Clausewitz in the twenty-first century - edited by Hew Strachan and Andreas Herberg-Rothe (Oxford University Press, 2007)
Clausewitz's On War has, at least until very recently, been regarded as the most important work of theory on its subject. But since the end of the Cold War in 1990, and even more since the 9/11 attacks on the United states in 2001, an increasing number of commentators have argued that On War has lost its analytical edge as a tool for understanding war. They have argued that Clausewitz was concerned solely with inter-state war and with properly defined armies, and that the sorts of conflicts which he discussed are therefore part of a historical pattern which dominated Europe between 1648, the end of the Thirty Years War, and 1990 itself